2017
DOI: 10.1038/s41467-017-01733-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of flexoelectricity in PbTiO3/SrTiO3 superlattice polar vortices using machine learning and phase-field modeling

Abstract: Flexoelectricity refers to electric polarization generated by heterogeneous mechanical strains, namely strain gradients, in materials of arbitrary crystal symmetries. Despite more than 50 years of work on this effect, an accurate identification of its coupling strength remains an experimental challenge for most materials, which impedes its wide recognition. Here, we show the presence of flexoelectricity in the recently discovered polar vortices in PbTiO3/SrTiO3 superlattices based on a combination of machine-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 41 publications
2
63
0
Order By: Relevance
“…Note that, as the elastic coefficients slightly change with the change of mole fraction x, the elastic coefficients of Flexoelectricity, the electromechanical coupling between the polarization and strain gradient (direct effect) or mechanical stress and electric eld gradient (converse effect), is a property of all insulators. 48 The exoelectric coupling energy density is expressed as: [48][49][50][51] f…”
Section: Phase Eld Model Of Cgfes Based On the Ginzburg-landau Theorymentioning
confidence: 99%
“…Note that, as the elastic coefficients slightly change with the change of mole fraction x, the elastic coefficients of Flexoelectricity, the electromechanical coupling between the polarization and strain gradient (direct effect) or mechanical stress and electric eld gradient (converse effect), is a property of all insulators. 48 The exoelectric coupling energy density is expressed as: [48][49][50][51] f…”
Section: Phase Eld Model Of Cgfes Based On the Ginzburg-landau Theorymentioning
confidence: 99%
“…Other imaging modes such as 4D STEM, promise further increases in both spatial resolution and data dimensionality. [7][8][9] The data can be much more precise [10][11][12] and quantitative 13,14 allowing, subtle details, such as changes in shape, to be directly related to various physical properties 13,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…ilkj ijkl f f = It has been shown that the static flexocoupling induces imprint [14,15,16], internal bias [17,18] and dead layer effect [19,20] in ferroelectric thin films, and vortices in superlattices [21].…”
Section: Introductionmentioning
confidence: 99%